HUBUNGAN BEBAN KERJA DENGAN STRES KERJA PADA PERAWAT DI RUANG ICU RSUD dr. H. MOH. ANWAR SUMENEP - Sugesti Aliftitah; Elyk Dwi Mumpuningtias; Imam Muttaqin (Wiraraja Medika : Jurnal Kesehatan, 2018)
Stress is an excessive workload, feelings of distress and emotional tension that impedes individual performance. The nurses' work stress can be attributed to the nurse's primary duties and responsibilities, heavy workloads, and leadership types. This type of research was analytic with Cross Sectional research design. In this research, the independent variables are workload and the dependent variable is the nurses' work stress. One month research time in ICU Room dr. H. Moh. Anwar Sumenep, sample17 respondents with total population sampling technique. Questionnaire research instrument and observation sheet, data analysis using Spearman with α (0,05). The results of most of the workload of nurses were moderate 9 (52,9%). Most of the work stress of nurse is light 10 (58,8%) .The data analysis obtained p value (0,031) <α (0,05) then H0 rejected which mean there is relation of work load with nurses work stress in ICU Room dr. H. Moh Anwar Sumenep. Efforts to suppress the work stress of nurses ICU dr. H. Moh.AnwarSumenep done by applying a service system in favor of nurses. Nurses should also enjoy the world of work and try to create a conducive working environment.